International Double Taxation and the Methods Treat - حسين نور حمزة (Journal of Legal Sciences, 2020)
The Phenomena of Double Taxation becomes a problem that all countries suffer from it specially developing countries where the double taxation becomes an obstacle before investments. Thus the world countries attempt to find a solution or this problem through national and international agreements